If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -5) = 7y + 8 Reorder the terms: 2(-5 + y) = 7y + 8 (-5 * 2 + y * 2) = 7y + 8 (-10 + 2y) = 7y + 8 Reorder the terms: -10 + 2y = 8 + 7y Solving -10 + 2y = 8 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -10 + 2y + -7y = 8 + 7y + -7y Combine like terms: 2y + -7y = -5y -10 + -5y = 8 + 7y + -7y Combine like terms: 7y + -7y = 0 -10 + -5y = 8 + 0 -10 + -5y = 8 Add '10' to each side of the equation. -10 + 10 + -5y = 8 + 10 Combine like terms: -10 + 10 = 0 0 + -5y = 8 + 10 -5y = 8 + 10 Combine like terms: 8 + 10 = 18 -5y = 18 Divide each side by '-5'. y = -3.6 Simplifying y = -3.6
| 3y-2x=m | | N^2-81n=0 | | -9p-4=50 | | -8(n-1)=5-8n | | -9p-4=40 | | =9E-07(551.368) | | 49=413c-7 | | 10(3x-5)=100x | | -5(4y-2)-y=-4(y-2) | | 6n+3n+3120=5400 | | -6+-1y=10 | | -7p-4=2p+40 | | 17=102 | | 6+-1y=10 | | 2(3s+2)=76 | | -4.9m^2+34.3m+0=58.8 | | 10(2x-11)=90x | | 2x+Y+4z=19 | | 12=15-9(3) | | 4x+2x-x= | | 13+(29+7)=13+(7+29) | | -5(x+3)=-14-4x | | R=4x+12 | | 3-(3x-6)=2+5x | | C(m)=0.5m+25 | | 5(2l+7)=55 | | 6z^2+7z+2=0 | | 9(x-2)=-3x+78 | | R=5x-16 | | .5555(9x+12)=10 | | 4-7(1-2v)=-33+8v | | p^2=2p+8 |